Heparin - A Century of Progress - Lever, Rebecca; Mulloy, Barbara; Page, Clive P. (Handbook of Experimental Pharmacology,, 2012)
Heparins remain amongst the most commonly used drugs in clinical practice.  Almost 100 years have passed since the initial discovery of this complex substance and, during this time, understanding of the nature and uses of heparin and related molecules has grown dramatically. The aim of this volume is to summarise the developments that have led to the current status of both heparins as drugs and the field of heparin research, with a focus on the particularly rapid progress that has been made over the past three decades. Individual sections are dedicated to the nature of heparin as a biological molecule, the current approaches and techniques that are used to ensure the safety and reliability of heparin as a medicine, the clinical pharmacology of heparin as an anticoagulant drug, effects and potential applications of heparin aside of those involving haemostasis and, finally, the nature and potential uses of heparin-like materials from both natural and synthetic sources.